Antioxidant Mechanism of Renal and Hepatic Failure Prevention Related to Paracetamol Overdose by the Aqueous Extract of Amblygonocarpus andongensis Stem Bark. (21st July 2022) - Baponwa, O.; Amang, A. P.; Mezui, C.; Koubala, B. B.; Siwe, G. T.; Vandi, V. L.; Tan, P. V.
Abstract : Paracetamol is a commonly used analgesic/antipyretic whose long-term intake or overdose is associated with renal and hepatic injuries. The aim of this study was to determine the hepatonephroprotective mechanisms of the aqueous extract of Amblygonocarpus andongensis stem bark (AEAASB) on renal and hepatic failure resulting from paracetamol overdose. Forty-five rats were divided into nine groups (n = 5 ); these were treated once daily for 8 days with 5 ml/kg distilled water (normal, negative, and satellite controls); 0.9% normal saline and 140 mg/kg N-acetyl-cysteine (positive controls); 125, 250, and 500 mg/kg AEAASB (test groups); and 500 mg/kg AEAASB (satellite test). On day 8 after different treatments, hepatonephrotoxicity was induced in all the groups except the normal group by oral administration of a single dose of paracetamol (1000 mg/kg). Urinary, hematological, serum, and oxidative stress parameters and in vitro antioxidant activity of AEAASB were evaluated. Histological sections of the liver and kidney were performed. AEAASB significantly decreased urea, creatinine, transaminases, alkaline phosphatase, and bilirubin (p < 0.001 ) at 500 mg/kg compared to the negative control. Significant decreases in hepatic (p < 0.01 ) and renal (p < 0.001 ) malondialdehyde levels were associated with increases in superoxide dismutase, catalase, and reduced glutathione levels in 500 mg/kg AEAASB compared with the negative control. Histological analysis showed that AEAASB prevented paracetamol-induced renal and liver tissue damage. Furthermore, AEAASB revealed a very strong antioxidant activity (inhibitory concentration 50 = 180   μ g / ml, antioxidant   activity   index = 5.55 ) with an ability to scavenge 63.03% 2, 2-diphenyl-2-picrylhy-drazyl radical and reduced ferric iron by 52.68 mgEqVitC/100 g DM. The hepatonephroprotective effect of AEAASB might result from its ability to improve the antioxidant status through the stimulation of antioxidant factors and the scavenging of free radicals. This property could be ascribed to the presence of some classes of bioactive compounds such as phenolic compounds in great amounts.